Analysis of The Role of Islamic Economics in Improving National Economic Resilience - Efendi Sugianto (Nomico, 2025)
This study aims to evaluate the contribution of Islamic Economics in strengthening national economic resilience through a quantitative approach. Islamic economics, with its principles of justice, equity, and sustainability, offers comprehensive solutions to modern economic challenges. This study used secondary data involving economic indicators, such as financial stability, wealth distribution, and the level of financial inclusion. The main instruments analyzed include zakat, infaq, waqf (ZISWAF), Islamic banking, and sukuk, which serve as driving pillars in the Islamic economic system. Statistical methods, such as regression analysis and correlation tests, are used to identify the impact of these instruments on national economic resilience variables. The results showed that the implementation of Islamic economics significantly contributed to the reduction of social inequality, improved public welfare, and a decrease in systemic economic risk. By promoting the values of Maqasid Sharia, the Islamic economic system not only promotes long-term economic stability, but also creates an inclusive and sustainable economic ecosystem. The study provides empirical evidence supporting the widespread adoption of Islamic economic policies as a framework for resilient and equitable national development amid global economic dynamics.